The impact of inequality on social value orientation: an eye-tracking study - Wang, Qian-Hui; Wei, Zi-Han; Chen, Wan-Ning; Na, Yu; Gou, Hui-Ming; Liu, Hong-Zhi (Frontiers in Psychology, 2025)
IntroductionResearchers have developed the social value orientation (SVO) framework to describe prosocial tendencies. However, existing tools for measuring SVO lack sufficient attention to the effect of option inequality, driven by the inequality-aversion motive. In this research, we conducted an eye-tracking experiment to compare the traditional SVO measure with the inequality-controlled condition, investigating how it influences estimated SVO values and underlying process mechanisms.MethodsA within-subjects eye-tracking experiment was conducted with 65 university students recruited from a university’s human subjects pool. Participants received 20 yuan (RMB; approximately US $2.9) in cash for their participation.ResultsSVOs were lower in the inequality-controlled condition than in the traditional SVO measure. Information processing, including complexity, depth, and direction, differed when fairness was controlled. The predictive effect of relative time advantage was also enhanced under controlled inequality conditions. In addition, the predictive effect of relative time advantage was stronger when controlling for option inequality, suggesting that controlling for option inequality enhances bottom-up information processing.DiscussionThese findings suggest that traditional SVO measures may overestimate prosocial tendencies due to a lack of inequality control. The study highlights the role of fairness evaluation in SVO assessments and provides insights into the cognitive mechanisms underlying prosocial decision-making, offering guidance for future SVO measurements.